Selection of high quality path through MXAODV in mobile ad-hoc network. (2019) - Sharma, Anupama; Bansal, Abhay; Rishiwal, Vinay
Selection of high quality path in mobile ad-hoc network is a critical issue due to mobility of nodes and variable channel conditions during data transmission. Path containing smallest number of hops generally performs less due to some links on those paths may have low or marginal quality. Mean loss ratio of link is also not a perfect way to estimate link quality, mean channel condition is not realistic. Hence, link quality estimation on the basis of loss ratio in burst loss conditions of different channels is significant. Incorporation of loss variance for a link in its quality estimation through modified expected transmission count (mETX) is the main aim of the proposed protocol to improve the communication efficiency in mobile ad-hoc networks. This paper describes the design and implementation of proposed routing protocol named as modified expected transmission count enabled ad-hoc on-demand distance vector (MXAODV). Extensive simulation has been done to analyse the performance of MXADOV. Significant improvements found in terms of throughput, packet delivery fraction, normalised routing load and end-to-end delay.